Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe The Power of Two terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VII SMP Negeri 22 Padang - PEGI DESVIKA DP (Departemen Matematika, 2019)
Mathematicallconcept understanding is onetoffthe learning objectivesx of mathematics that mustsbe achieved byy students. But, learning activities in schools have not been optimal in facilitating students to improve the understanding of mathematical concept. Onepeffort toxovercome thissproblem is to applys the cooperativex learning model typeoThe Powerrof Twoo. The purpose of this researchh is to describe whether mthematicalkconceptjunderstandingk of students whoplearn to use thejmodel cooperative learning ThecPower ofkTwo are better than mthematical concept understandinghof studentsrwho learnpby direct learning. The typegof researchdwas a quasy experimentt with StaticvGroupfDesign. The reserch hypothesi was proven by tutest. Basedmon thelresults ofgdataa analisis, itcwaspconcluded ihat the mathematial conceptt understanding of studentsgwhoylearn to use the model cooperativenlerning The Power of Two are better than students who learn with direct learningg in class VII junior high school 22 Padang. Then, the development of student’ mathematicall concept understanding during the implementation of ThekPowerkofkTwo cooperative learningmmodel hass increased. Keywords — direct learning, mathematicalvconcept, ThenPowerrofhTwoocooperative learningnmodel.